Purification of wedelolactone from Eclipta alba and evaluation of antioxidant activity. Issue 17 (22nd November 2017) - Ding, Hui; Wang, Yongqiang; Gao, Yujie; Han, Xu; Liu, Shejiang; Tang, Guiwen; Li, Jiaqi; Zhao, Dan
ABSTRACT: A hybrid chromatography-crystallization process to purify wedelolactone obtained from Eclipta alba was developed. The crude extract was obtained by microwave-assistant extraction and purified by silica gel column chromatography in which dichloromethane–methanol–acetic acid solution was used as the eluent. Dilution crystallization was employed to perform the final purification. To optimize the processing parameters, single factor analysis and response surface methodology were employed. The results indicated that the purification yield and purity of wedelolactone could reach 77.66% and 99.46%, respectively. Antioxidant assays showed that the products had strong antioxidant and free radical scavenging activity which was close to oligomeric proantho cyanidins.